Analysis of Technology Integration in Teacher Education in Ghana - Douglas D. Agyei (Journal of Global Initiatives, 2013)
Ghana’s Education Reforms launched in June 2007 introduced Computer literacy not on-ly as a new subject, but also as a tool to enhance teaching and learning. This study pro-vides a situational analysis of the pedagogical issues associated with Information and Communication Technology (ICT) use in teacher education in Ghana. The methodology used in the study focused on meta-data analysis in which issues associated with integrat-ing ICT in Ghana’s education were re-examined to provide a better picture that will sup-port future achievement of teaching and learning with ICT. The evidence suggests that the challenges of ICT use in education do not lie only in the lack of availability of tech-nological resources, but also in the shortage of skilled human resources and other institu-tional factors. Implications that relate to teacher “readiness” to deliver 21st century edu-cation through the use of technology are discussed and analyzed.